Social Media and Sales Performance of Clothing Small Businesses in Nigeria - Tolulope Adetayo Fajobi (Research Synergy Foundation, 2023)
In Nigeria, small businesses are increasingly turning to social media as an approach for marketing and boosting their sales due largely to its wide reach and cost-effectiveness. The clothing industry is no exception, as small clothing businesses in Nigeria have begun to leverage social media to reach a wider audience and increase sales performance. Apparently, despite the huge potential of social media platforms available to prospective small businesses in Nigeria, existing and prospective small business owners still struggle to utilise these platforms to improve sales performance in the country. The paper examined the level of contributions of social media on small businesses' sales performance vis-a-vis customers purchasing behaviour. Also, it explored inherent challenges clothing businesses encountered on social media platforms for improved sales performance. The study was centred on descriptive research design through a qualitative approach, which relied on interviews. For the study, a purposive sampling technique was used to select 18 participants in the clothing business (shoes, fashion clothes, hairdressing and fashion accessories and hairdressing). By implication, social media usage has a multiplier effect on small businesses vis-à-vis the economic transformation of Nigeria if harnessed in line with the function framework. The study concluded that there is an apt need for small clothing businesses in Nigeria to grasp the trajectories and dynamics of social media and engage in effective and sustainable strategies to leverage social media for optimum benefit.